THE USE OF ENGLISH SONGS TO IMPROVE STUDENTS’ VOCABULARY MASTERY - Moh Wardiman; Aminah Aminah; Anjar Dewi (Tadulako University, 2022)
The idea of this research was based on the researcher’s experiences. Songs have a big role in helping the researchers to increase the vocabulary mastery so that the purpose of the study was to find out the use of English song in improving students’ vocabulary mastery. In conducting this reseach, researchers took the 2019 batch English students in Tadulako University as the respondent. While the researchers used purposive sampling to take 30 students as the sample. in order to answer the research questions, this study used the questionnaire. The researchers distributed the questionnaire to the students by using Google form. Based on the research findings, it could be seen in the responds of the participants. The participants found that every aspect in songs were able to be used to help them to have better development on their listening skill and even on the language elements (pronunciation, vocabulary, and grammar). It can be concluded that English songs can improve the students’ vocabulary mastery.